Radiographic Evaluation of Infraorbital Canal Protrusion into Maxillary Sinus Using Cone-Beam Computed Tomography - Fahrettin Kalabalık; Tunahan Aktaş; Ender Akan; Emre Aytuğar (eJournal of Oral Maxillofacial Research, 2020)
Objectives: The aim of this retrospective study was to evaluate the relation of the infraorbital canal course with the maxillary sinus using cone-beam computed tomography.